The happy-fish-little-pond effect on enjoyment: Generalizability across multiple domains and countries. (June 2023) - Basarkod, Geetanjali; Marsh, Herbert W.; Guo, Jiesi; Parker, Philip D.; Dicke, Theresa; Pekrun, Reinhard
Abstract: Academic enjoyment is an important educational construct given that it benefits students' engagement, persistence, wellbeing, and mental health. In this study, we examine two factors that determine this crucial emotion, namely student- and class-level achievement. Past research has been restricted to single-country or single-domain examinations of secondary school students, limiting generalizability of findings. To bridge this gap, we utilize the Trends in International Mathematics and Science Study and the Progress in International Reading Literacy Study (TIMSS-PIRLS) combined 2011 data ( N = 180, 084 4th-grade students, 37 countries). Our results provide robust evidence that student-level achievement positively predicts enjoyment in math, science, and reading, while the effects of class-level achievement are negative—the Happy-Fish-Little-Pond Effect. These results showed relative universality across the domains and countries examined. Highlights: We tested two predictors of enjoyment across three domains and 37 countries. Student achievement positively predicted enjoyment in math, science, and reading. Class-average achievement negatively predicted enjoyment in all three domains. Effects were relatively universal across countries in direction but varied in size.